The value, degree, and consistency of Kansas crop farms’ relative characteristics, pratices, and management performances - Morris, Cooper H., Jr (Kansas State University, 2014)
This research analyzes how crop farms can achieve a higher net income per acre than other operations by farming fundamentally differently than others. There are many factors that are important to the long-term viability of today’s crop operations, one of which is how farms profitability compares with other operations. This determines farms’ ability to compete for land, outlast other operations through periods of unprofitability, and produce crops at long run equilibrium prices. These factors are relevant in today’s crop production industry where farms sit on a segment of the agribusiness supply chain. Therefore, in the interest of providing farms relevant information to manage their operations, this research analyzes how farms can distinguish their performance from other operations by accessing land and equipment resources, production practices for growing crops, and focusing their management efforts differently than other operations. There are three parts to this analysis. First, farms are broken down by characteristics, practices, and management performances. Then an econometric analysis quantifies the integrated correlation between farms’ distinguished characteristics, practices, and management performances and their distinguished net incomes per acre. Next a standard deviation analysis measures the degree to which farms are capable of distinguishing particular characteristics, practices, and management performances from other operations. Lastly, the performance of farms over the 2001 to 2010 time period is used to quantify how feasible it is for farms to maintain particular differences from other operations. Data used in this analysis were provided by the Kansas Farm Management Association, Kansas State University’s Department of Agricultural Economics, and Kansas’s National Agricultural Statistics Service office. The results suggest the way farms distinguish their characteristics, practices, and management performances from other operations impacts how their net income compares to other operations. The econometric analysis found that relative farm size, share of rented acres, the value of overhead and equipment investment per acre, government payments, planting intensity, risk, and cost, yield, and price management performances were all significantly related to farms’ relative net income. In regards to farms’ comparative profitability, this suggests farms should be aware of how their characteristics, practices, and management performances compare to other operations. The results also suggest the degree to which and the consistency with which farms can distinguish particular characteristics, practices, and management performances are different from one another. Over the 2001 to 2010 period, Kansas farms distinguished their characteristics from other operations to a larger degree than they distinguished their practices and management performances. Farms also maintained differences in their characteristics more consistently than they maintained differences in their practices and management performances. This suggests farms that are actively seeking to distinguish their net income per acre from other operations should be aware of the degree and consistency with which they can maintain particular differences from other operations.
Keywords: Production; Agriculture; Agribusiness; Strategy; Economics; Agriculture, General (0473)